Beta Decay Properties of Waiting-Point N = 50 and 82 Isotopes - Necla Çakmak; Najm Abdullah Saleh (Particles, 2025)
We performed the microscopic calculation of <semantics>β</semantics>-decay properties for waiting-point nuclei with neutron-closed magic shells. Allowed Gamow–Teller (GT) and first-forbidden (FF) transitions were simulated using a schematic model (SM) for waiting-point N = <semantics>50,82</semantics> isotopes in the framework of a proton–neutron quasiparticle random phase approximation (<semantics>pn</semantics>-QRPA). The Woods–Saxon (WS) potential basis was used in our calculations. The <semantics>pn</semantics>-QRPA equations of allowed (GT) and (FF) transitions were utilized in both the particle–hole (<semantics>ph</semantics>) and particle–particle (<semantics>pp</semantics>) channels in the SM. We solved the secular equations of the GT and FF transitions for eigenvalues and eigenfunctions of the corresponding Hamiltonians. A spherical shape was assigned to each waiting-point nucleus in all simulations. Significantly, this study marks the first time that <semantics>β</semantics>-decay analysis has been applied to certain nuclei, including 82Ge50, 83As50, 84Se50, 85Br50 and 87Rb50 with <semantics>N=50</semantics> isotones, and 132Sn82, 133Sb82, 134Te82, 135I82 and 137Cs82 with <semantics>N=82</semantics> isotones. Since there is no prior theoretical research on these nuclei, this work is a unique addition to the field. We compared our results with the previous calculations and measured data, and our calculations agree with the experimental data and the other theoretical results.